Application of Mosley’s Analytical Framework adopting the Logistic Regression to under five Child Mortality in Gezira State - Yousif, Huda Mubarak (Gezira Journal of Health Sciences, 2015)
This study aims to enhance and to review the research methodology in the area of under-five mortality and to investigate its most underlying causes. Mosley's framework focuses on the environmental, demographic, social, and economic factors affecting mortality of children under five years. The study population consisted of households in Gezira state. The sample consisted of 1000 households that have at least one child under five years (alive or dead) distributed between the seven localities, using the number of households in Gezira state in each locality as a sub sample frame and then applying stratified random sampling with probability proportional to size for determining the sample size in each of the administrative unit in each locality. Data was collected through questionnaires and was statistically analyzed using Statistical Packages for Social Sciences (SPSS) and Micro Stat software. In addition to frequencies tables, descriptive statistics, statistical tests, cross tabulations and regression analysis were utilized for test of research hypotheses. Important results reveal that the factors affecting under five mortality are the duration of breastfeeding, the type of toilet, the age of the mother, raising animals in or around the house, educational level of the mother, father occupation, and educational level of the father, contraceptive usage, vaccination of tetanus during pregnancy, and finally the number of rooms in the house.